A CASE OF THE 'SEVERAL-YEAR ITCH'. Issue 12 (15th November 2016) - Woodward, Christopher; Wynford-Thomas, Ray; Wardle, Mark
Abstract : A 36-year-old lady reported a significant, uncontrollable itch inside her nose, which had been ongoing for a few years. She also reported a 6-week history of daily headaches which worsened with coughing. On examination she had evidence of mild papilloedema. Otherwise her examination was normal. MRI brain showed a well-defined enhancing mass, measuring 12.1×11×7.3 mm, within the fourth ventricle. She was referred to the neurosurgeons who felt that the mass was most likely an ependymoma, for which surgical resection is planned. A small number of cases of fourth ventricle floor tumours have been reported to cause pruritus of the nostrils, which can often be severe. A potential explanation is offered by early animal experiments which suggested the presence of a "scratching centre" in the medulla oblongata. It is now known that the spinal nucleus of the trigeminal nerve is located near the floor of the fourth ventricle and thus it is felt that disruption in this area can result in pruritus. This case is important as an example of a pathology that can be localised by a very specific symptom, which may be easily overlooked, and which pre-dates more obvious symptoms of a space-occupying lesion.